Draft Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Volume II (Annexures) Government of Kerala - Planning Commission (Planning Commission, 2002)
Draft Tenth Plan 2002-2007 and Annual Plan 2002-2003: Proposed Outlays Physical Targets and Achievements Draft Tenth Plan Proposals for Spillover and Ongoing Programmes/Projects Draft Tenth Plan (2002-2007) Proposals for Maximising Benefits of Completed Programmes/Projects Draft Tenth Plan (2002-2007) - Proposals for Programmes/Projects - New Schemes Summary Statement Statement Regarding Externally Aided Projects Draft Tenth Plan (2002-2007) and Draft Annual Plan 2002-2003 - for District Plans, Centrally Sponsored Schemes Pradhan Mantri Grammoudyog Yojana- Outlay and Expenditure
State Planning Board